2021
DOI: 10.1111/ppl.13383
|View full text |Cite
|
Sign up to set email alerts
|

Visible light regulates anthocyanin synthesis via malate dehydrogenases and the ethylene signaling pathway in plum (Prunus salicina L.)

Abstract: Light regulates anthocyanins synthesis in plants. Upon exposure to visible light, the inhibition of photosynthetic electron transfer significantly lowered the contents of anthocyanins and the expression levels of key genes involved in anthocyanins synthesis in plum fruit peel. Meanwhile, the expression levels of PsmMDH2 (encoding the malate dehydrogenase in mitochondria) and PschMDH (encoding the malate dehydrogenase in chloroplasts) decreased significantly. The contents of anthocyanins and the levels of the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…For example, exogenous ethylene increases anthocyanin accumulation in grape berries by up-regulating the expression of anthocyanin structural genes [ 19 ]. Similar results are reported in plum [ 20 , 21 ], apple [ 22 ], and strawberry [ 23 ]. In apple, two ethylene response factors, MdERF1B and MdERF3, are key positive regulators of anthocyanin biosynthesis in response to ethylene signals [ 24 ].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, exogenous ethylene increases anthocyanin accumulation in grape berries by up-regulating the expression of anthocyanin structural genes [ 19 ]. Similar results are reported in plum [ 20 , 21 ], apple [ 22 ], and strawberry [ 23 ]. In apple, two ethylene response factors, MdERF1B and MdERF3, are key positive regulators of anthocyanin biosynthesis in response to ethylene signals [ 24 ].…”
Section: Introductionsupporting
confidence: 86%
“…In many fruit tree crops, fruit ripening is usually accompanied by anthocyanin accumulation, and ethylene is considered an anthocyanin activator in plants. Several studies have confirmed that ethylene induces red/purple coloration by activating anthocyanin production in apple, plum, grape, and strawberry [ 19 , 20 , 21 , 51 ]. However, ethylene inhibited anthocyanin accumulation in Arabidopsis [ 26 ], pear [ 27 ], and immature fruits of Fragaria chiloensis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the development of green tissues (such as leaves, flower buds, and stems) and tissue-cultured cells, light promotes the accumulation of anthocyanins by activating gene transcript levels related to anthocyanin metabolic pathways ( Uleberg et al., 2012 ; Zhang et al., 2021a ). In the early stages of anthocyanin synthesis, the expression patterns of related genes can be regulated by different light qualities and intensities, and this expression pattern is dramatically changed and accompanied by distinct species.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the high UV radiation to which deciduous fruit trees are subjected can influence the physiology of the plant. Positively, visible and UV light regulate anthocyanin synthesis in Japanese plums in the photosynthesis-respiration interaction by controlling malate metabolism through malate dehydrogenase and the ethylene ATP signaling pathway (Zhang et al, 2021). Adversely, the high UV radiation in the tropical highlands causes sunburn on the fruits, which greatly affects the marketability of the fruit and, therefore, the productivity of the crop (Fischer, Orduz-Rodríguez et al, 2022).…”
Section: Ecophysiology Altitude Light and Solar Radiationmentioning
confidence: 99%